2015
DOI: 10.1016/j.neuropharm.2014.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and norepinephrine receptors participate in methylphenidate enhancement of in vivo hippocampal synaptic plasticity

Abstract: Attention-deficit hyperactive disorder (ADHD) is the most commonly studied and diagnosed psychiatric disorder in children. Methylphenidate (MPH, e.g., Ritalin) has been used to treat ADHD for over 50 years. It is the most commonly prescribed treatment for ADHD, and in the past decade it was the drug most commonly prescribed to teenagers. In addition, MPH has become one of the most widely abused drugs on college campuses. In this study, we examined the effects of MPH on hippocampal synaptic plasticity, which se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 81 publications
1
29
0
1
Order By: Relevance
“…In the present work, we found systemic METH treatment enhances DG‐LTP in rats. These data are consistent with a recent report showing a similar effect for methylphenidate on DG‐LTP (Jenson et al, ). The DG receives dopaminergic innervation from VTA and contains dopamine D1/D5 receptors (Fremeau et al, ; Gangarossa et al, ; Meador‐Woodruff et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present work, we found systemic METH treatment enhances DG‐LTP in rats. These data are consistent with a recent report showing a similar effect for methylphenidate on DG‐LTP (Jenson et al, ). The DG receives dopaminergic innervation from VTA and contains dopamine D1/D5 receptors (Fremeau et al, ; Gangarossa et al, ; Meador‐Woodruff et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The dentate gyrus (DG) is one of hippocampal areas involved in several forms of synaptic plasticity, such as long‐term potentiation (LTP) (Blaise and Hartman, ). Different addictive drugs have been shown to modulate synaptic plasticity in the DG (Creed and Lüscher, ; Hu et al, 2012; Jenson et al, ; Lüscher and Malenka, 2011). Methamphetamine (METH) is one of the most abused psychostimulants.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological evidence demonstrated that D1 and D5 receptors are important for controlling spike timing dependent plasticity within the hippocampus (Yang and Dani, 2014). Also, there is functional evidence that indicates that drugs of abuse, such as nicotine (Tang and Dani, 2009; Zhang et al, 2010) and methylphenidate (Jenson et al, 2015), recruit dopaminergic neurotransmission to influence synaptic plasticity within the hippocampus. Dopaminergic neurotransmission in the hippocampus during specific time points in the retention interval also seem to be important for successful consolidation of long-term memories (Rossato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The dopaminergic system was shown to mediate the antinociceptive effects of N 2 O [24], and levels of central neurotransmitters, dopamine (DA), and norepinephrine (NE) were significantly elevated after repeated N 2 O exposure in CD-1 mice [25]. Dysregulation of both catecholamine systems has been implicated in ADHD [26].…”
Section: Introductionmentioning
confidence: 99%